Comparative analysis of textural properties of SBA-15 prepared from rice husk and tetraethylorthosilicate. - Van, Thanh Ho (Vietnam Journal of Chemistry, 2012)
SBA-15 materials were synthesized using rice husk. In addition, SBA-15 was synthesized by using tetraethylorthosilicate as a reference material. The obtained materials were characterized by XRD, TEM and adsorption/desorption nitrogen method. Though less ordered hexagonal mesoporous SBA-15 materials could be obtained from rice husk they exhibit high surface area and large pore size in comparison with one from tetraethylorthosilicate. Morphology of SBA-15 prepared from rice husk consists of curve-rod like silicas while that of SBA-15 from tetraethylorthosilicate consists of rod-like silicas. The difference in mesoporous tubular structure and textural properties of synthesized SBA-15 could be assigned to inherent impurities of metal ions in rice husk.